(untitled) (ModaPalavra e-periódico, 2018)
This article aims to present na analysis of the early stages of the product development process in fashion and clothing, seeking to outline how the information is used by the designer, as a professional responsible for creating. With the lócus of Recife city, Brazil, and as an object of research in creative companies of Fashion Design (clothing, footwear and accessories), is presented as a guiding question the following approach: how the creative fashion industry professionals combine creativity and inspiration with the information that they are external, such as fashion trends and market, in the process of creation of this sector? From a survey of exploratory and descriptive character, based on semi-structured interviews with professionals responsible for creative development in companies, it was possible to raise considerations about the creative process of these professionals and the mechanisms that cover the constant exercise that involves the maintenance of strategic information in the development of creative projects.Lorem ipsum dolor sit amet, consectetur adipiscing elit, sed do eiusmod tempor incididunt ut labore et dolore magna aliqua. Ut enim ad minim veniam, quis nostrud exercitation ullamco laboris nisi ut aliquip ex ea commodo consequat. Duis aute irure dolor in reprehenderit in voluptate velit esse cillum dolore eu fugiat nulla pariatur. Excepteur sint occaecat cupidatat non proident, sunt in culpa qui officia deserunt mollit anim id est laborum.